Role of CD61(+) cells in thrombocytopenia of dengue patients - Noisakran, Sansanee (2012)
Although hematological disorders with salient features of thrombocytopenia have been well documented in dengue patients, the role of CD61-expressing platelets and the megakaryocytic cell lineage in the pathogenesis of dengue virus (DENV) infection remains largely unexplored. A prospective observational study was performed using blood samples and PBMCs from dengue-confirmed patients, as well as from rhesus monkeys (RM) experimentally infected with DENV. Immunohistochemical staining and FACS techniques were applied to evaluate the frequencies of CD61(+) cells that contained DENV antigen. Highly enriched population of CD61(+) cells was also isolated from acute DENV-infected RM and assayed for DENV RNA by quantitative RT-PCR. Results revealed that DENV antigen was found in small vesicles of varying size, and more frequently in anucleated cells associated with platelets in dengue patients. The DENV antigen-containing cells were CD61(+) and appeared to share characteristics of megakaryocytes. Kinetic profiles of CD61(+) cells from DENV-infected RM revealed a transient increase in CD61(+)CD62P(+) cells early after DENV infection. DENV RNA in a highly enriched population of CD61(+)cells from the infected RM was observed during acute stage. Our results indicate that virus containing CD61(+) cells may be directly linked to the platelet dysfunction and low platelet count characteristics of dengue patients.